Exploring the directionality in the relationship between descriptive and injunctive parental and peer norms and snacking behavior in a three-year-cross-lagged study - K. E. Bevelander; W. J. Burk; C. R. Smit; T. J. van Woudenberg; L. Buijs; M. Buijzen (BMC, 2020)
Abstract Background People's eating behavior is assumed to be influenced by what other people do (perceived descriptive norms) and what others approve of (perceived injunctive norms). It has been suggested that adolescents are more susceptible to peer norms than parental norms, because they experience a strong need for group acceptance that leads to conforming to peer group norms. The current study examined changes in snacking behavior and four types of social norms (i.e., parental and peer descriptive and injunctive norms) that promoted fruit and vegetable intake among adolescents. This study was the first to examine whether snacking behavior also influenced norm perceptions by testing the directionality of these associations. Methods The study consisted of 819 participants (M [SD] age = 11.19 [1.36]; 46.1% boys), collected at three time points (T1 = 2016, T2 = 2017 and T3 = 2018) during the MyMovez project. Self-reported frequency of snack consumption, perceived parental and peer descriptive and injunctive norms were assessed. The primary analysis consisted of a series of cross-lagged autoregressive models specified in a structural equation modeling framework. Results Model comparisons testing the descriptive and injunctive norms in separate models and in an additional combined model revealed evidence for bi-directional associations between norms and snacking behavior. Descriptive peer and parent norms were not found to have an effect on subsequent snacking behaviors. Perceived injunctive parental norms were positively associated with healthy snack food intake and negatively associated with unhealthy snack intake (forward direction). Injunctive peer norms were negatively associated with healthy snack food intake. In addition, higher unhealthy snack food intake was negatively associated with the perception of descriptive and injunctive parental norms 1 year later (reversed direction). We did not find peer norms to be more closely associated with changes in snacking behaviors compared to parental norms. Conclusions Parents expecting their children to snack healthy had a positive influence on healthy snacking behavior whereas only acting as a healthy role model did not. Future research should address the possible interaction between descriptive and injunctive norms. Research should also take into account the bi-directional relations between eating behaviors and normative perceptions.